Crime and civilization: the birth of criminology in the early nineteenth century - Kivivuori, Janne (Clarendon studies in criminology, 2024)
Drawing on original French, German, and English publications, 'Crime and Civilization' explores the rise of data-based criminology as an intellectual field in continental Europe in the early nineteenth century, spanning from Enlightenment philosophers to the general rise of science in society.